Neurophenotype and genetic analysis of children with Aicardi‐Goutières syndrome in China - Shen Zhang; Weihua Zhang; Changhong Ding; Xiaotun Ren; Fang Fang; Yun Wu (Wiley, 2024)
ABSTRACT Importance Aicardi-Goutières syndrome (AGS) is a rare genetic disorder mainly affecting the central nervous system and autoimmunity. However, research on AGS among Chinese patients is limited. Objective To summarize the neurologic phenotypes and genetic causes in pediatric AGS patients, providing insights for early recognition and diagnosis in the Chinese population. Methods Clinical features and neuroimaging results of the patients diagnosed with AGS from Beijing Children's Hospital between January 2018 and January 2022 were collected. Whole exome sequencing was used for genetic analysis. Results A total of 15 patients was included, all presenting with various neurological symptoms, including developmental delay (100%), motor skill impairment (100%), language disability (78.6%), dystonia (93.3%), microcephaly (73.3%), sleep disorders (26.7%), regression (20.0%), vessel disease (6.7%), and epilepsy (6.7%). Neuroimaging revealed intracranial calcification (86.7%), cerebral atrophy (73.3%), and leukodystrophy (73.3%). Seven genes were identified, with TREX1 being the most common (40.0%, 6/15), followed by IFIH1 (20.0%, 3/15). Variant c.294dupA (p.C99Mfs*3) was detected in four unrelated patients, accounting for 66.7% (4/6) patients with the TREX1 variant. A literature review showed that TREX1 gene mutations in 35.6% (21/59) of AGS patients among the Chinese population. Interpretation Neurological symptoms are the most prevalent and severe presentation of AGS. Diagnosis may be considered when symptoms such as developmental delay, dystonia, microcephaly, brain calcification, and leukodystrophy emerge. TREX1 mutations are predominant in the Chinese population.